Multidimensional Responses to Disease Information: How Do Winegrape Growers React to Powdery Mildew Forecasts and To What Environmental Effect?. (28th March 2016) - Lybbert, Travis J.; Magnan, Nicholas; Gubler, W. Douglas
Abstract : Access to better information can enable adjustments that improve individual and social outcomes. In agriculture, accurate forecasts can be especially valuable to both producers and society at large. We analyze the impact of disease forecasts on the responses of growers along multiple margins of adjustment. Using high‐resolution plot‐level panel data, we analyze how California winegrape growers adjust powdery mildew control strategies in response to disease forecasts. While trials that allow only treatment timing adjustments suggest these forecasts bring large environmental benefits, in practice many growers simultaneously adjust what, when, and how much they spray. We find that the net environmental impact of this multidimensional response may actually be negative.